The Unique Identity of Humans and Mujahadah an-Nafs in Developing the Potential of Children from the Perspective of the Qur'an - Aba Billur Rohmah; Wiwin Ainis Rohtih; Ahmad Zainuddin; Miftara Ainul Mufid (Mauriduna : Journal of Islamic Studies, 2026)
This study analyzes the concept of developing child potential through the integration of unique human identity and mujahadah an-nafs from the perspective of the Qur'an. In this study, unique human identity is understood as individual characteristics that include biological aspects, character, and potential that distinguish each human being. This study uses a qualitative approach with a type of library research through the maudhu'i (thematic) interpretation method.. The study results indicate that the Qur'an views every human being as having individual characteristics that form the basis for developing their potential, while the mujahadah an-nafs functions as an internal control mechanism to direct and optimize that potential. The research findings confirm that the development of children’s potential will be more effective if parents’ external supervision is integrated with the formation of self-control based on Qur’anic values. The novelty of this study lies in the integration of the concept of unique human identity and mujahadah an-nafs as a conceptual model for developing children’s potential from a Qur’anic perspective. These findings have implications for strengthening family education models that respect the individual characteristics of children while building self-control as a foundation for developing their potential.